2019
DOI: 10.1111/ijn.12764
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care satisfaction from school‐aged children's perspective: An integrative review

Abstract: Aim: This integrative review synthesizes the current knowledge on school-aged children's satisfaction with nursing care in acute care settings.Background: Children identify aspects of nursing care that are not valued by their parents. This fact confirms the relevance of properly assessing children's satisfaction.Design: An integrative review was performed. . Twenty qualitative studies and three quantitative studies were included for revision and were analysed by two independent reviewers.Results: Three themes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 41 publications
0
14
0
17
Order By: Relevance
“…Children tended to prioritize the qualities of the nurse rather than specific elements of the role, so for example someone who listened, understood their needs, was kind and would stand up for them. Personal characteristics of nurses are consistently described by children when asked about their experiences of care; the nurse as a person is the most important factor (Loureiro, Figueiredo, & Charepe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Children tended to prioritize the qualities of the nurse rather than specific elements of the role, so for example someone who listened, understood their needs, was kind and would stand up for them. Personal characteristics of nurses are consistently described by children when asked about their experiences of care; the nurse as a person is the most important factor (Loureiro, Figueiredo, & Charepe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This review examined eligible studies using a two-criterion scale of research quality (high, moderate, or low) and data relevance (yes or no), which is suggested by Whittemore and Knafl (2005). For research rigor, a quality scoring system was adapted from a past integrative review (Loureiro, Figueiredo, & Charepe, 2019) supplemented by new items including ethical issues, rigor of data collection, and analysis, interpretation, and research implications (see Table S1). Quality scores ranged from 0 to 7 ("Yes" = 1 and "Unclear/No" = 0) and were summarized into three categories: low quality (0-3); moderate quality (4-5);…”
Section: Data Examinationmentioning
confidence: 99%
“…It is considered a care outcome and an important indicator of the quality of care. In pediatric hospitalization, which is a difficult event that disturbs the family and causes anguish, satisfaction is usually measured with the help of the parents as representatives of the child's interests (Loureiro et al, 2019). Moreover, in this context, parents see themselves as recipients of nursing care, so the dominant care philosophy, which is widely accepted as the best practice in pediatrics, is the philosophy of family-centered care (Shevell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%